Learning Motivation, Socioemotional Skills and School Achievement in Elementary School Students - Leilane Henriette Barreto Chiappetta-Santana; Ana Deyvis Santos Araújo Jesuino; Ariela Raissa Lima-Costa (Paidéia (Ribeirão Preto), 2022)
Abstract The motivation to learn is an element that drives student behavior and acts as a subjacent solving school demands, as well it influences the development and expression of socioemotional skills and school performance. This research constitutes a systematic review of the literature that investigated the relationship between motivation to learn, socioemotional skills and school performance in children enrolled in elementary school. A total of 9,631 abstracts from the ASSIA, EDUC, ERIC, PsycArticles, Science Direct, SCOPUS and Web of Science databases were examined, ending with 44 studies. The findings indicated a positive relationship between the three constructs, corroborating the literature that illustrates the benefits of various indicators of school and psychological well-being of children and adolescents to enhance learning and school performance. It is noteworthy that student-family and student-teacher interactions can favor student success or failure.